2016
DOI: 10.7717/peerj.2602
|View full text |Cite
|
Sign up to set email alerts
|

In silico study on anti-Chikungunya virus activity of hesperetin

Abstract: BackgroundThe re-emerging, Aedes spp. transmitted Chikungunya virus (CHIKV) has recently caused large outbreaks in a wide geographical distribution of the world including countries in Europe and America. Though fatalities associated with this self-remitting disease were rarely reported, quality of patients’ lives have been severely diminished by polyarthralgia recurrence. Neither effective antiviral treatment nor vaccines are available for CHIKV. Our previous in vitro screening showed that hesperetin, a biofla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 73 publications
(75 reference statements)
0
16
0
2
Order By: Relevance
“…In a similar study, Hesperetin was screened for potential inhibitory activities against four CHIKV's nonstructural proteins, namely nsP1, nsP2, nsP3 and nsP4 in addition to SPK2 via the docking of the compound to each protein. Hesperetin exhibited the strongest binding affinity against 3GPG (-8.5 kcal/mol), followed by nsP4 and SPK2 (-7.7 kcal/mol), nsP1 (-7.6 kcal/ mol) and finally 3TRK (-6.9 kcal/mol) [19] . Similarly, Suramin, an antiparasitic drug, several chemical compounds had been tested for its anti-CHIK activity by docking [20,21] .…”
Section: Resultsmentioning
confidence: 98%
“…In a similar study, Hesperetin was screened for potential inhibitory activities against four CHIKV's nonstructural proteins, namely nsP1, nsP2, nsP3 and nsP4 in addition to SPK2 via the docking of the compound to each protein. Hesperetin exhibited the strongest binding affinity against 3GPG (-8.5 kcal/mol), followed by nsP4 and SPK2 (-7.7 kcal/mol), nsP1 (-7.6 kcal/ mol) and finally 3TRK (-6.9 kcal/mol) [19] . Similarly, Suramin, an antiparasitic drug, several chemical compounds had been tested for its anti-CHIK activity by docking [20,21] .…”
Section: Resultsmentioning
confidence: 98%
“…In the same study, hesperetin, another flavanone which is found richly in citrus fruits, was found to exert most potent anti-CHIKV effect during the virus intracellular replication, with an IC 50 of 8.5 lM [1]. Molecular docking and molecular dynamics studies by Oo et al also revealed strong and stable interactions between hesperetin and CHIKV nonstructural protein 2 (nsP2) as well as non-structural protein 3 (nsP3), suggesting that these proteins may be the target of hesperetin's anti-CHIKV activity [101].…”
Section: Antiviral Activity Of Other Flavonoidsmentioning
confidence: 98%
“…nsP1, nsP2, nsP3, nsP4 and five structural proteins i.e. capsid (C), envelope glycoprotein E1, E2, E3 and 6k [7,11,17,21]. nsPs play a key role in the intracellular replication of CHIKV [17].…”
Section: Introductionmentioning
confidence: 99%
“…capsid (C), envelope glycoprotein E1, E2, E3 and 6k [7,11,17,21]. nsPs play a key role in the intracellular replication of CHIKV [17]. Inside the host cell, nascent single polypeptide P1234 is formed which is then cleaved to mature nsP4 and precursor P123 replication complex, which is further processed to produce nsp1 and P23 complex and finally the cleavage of P23 results in mature nsP1, nsP2, nsP3, nsP4 [11,22,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation